2011
DOI: 10.1055/s-0031-1296436
|View full text |Cite
|
Sign up to set email alerts
|

Two-way Crossover Bioequivalence Study of Alendronate Sodium Tablets in Healthy, Non-smoking Male Volunteers under Fasted Conditions

Abstract: This study was conducted in order to assess the bioequivalence of two different formulations containing 70 mg alendronate sodium (CAS 121268-17-5) under fasted conditions. One hundred twenty-two healthy male volunteers were enrolled in an open label, randomized, crossover design with a wash-out period of 20 days in one study center. Urine samples were collected up to 36 h post-dose, and the concentrations of alendronic acid were determined using a high performance liquid chromatographic method with pre-derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a classical, typical bioequivalence study, 122 subjects were enrolled because of the high within-subject CV for urine parameters, 37.42% for A e 0– t , and 40.05% for R max 19. Rhim et al20 were the first to assess the bioequivalence of alendronate by determining its plasma concentrations in a two-period crossover study involving 23 Korean subjects; the results demonstrated bioequivalence even though the study power was <60%.…”
Section: Discussionmentioning
confidence: 99%
“…In a classical, typical bioequivalence study, 122 subjects were enrolled because of the high within-subject CV for urine parameters, 37.42% for A e 0– t , and 40.05% for R max 19. Rhim et al20 were the first to assess the bioequivalence of alendronate by determining its plasma concentrations in a two-period crossover study involving 23 Korean subjects; the results demonstrated bioequivalence even though the study power was <60%.…”
Section: Discussionmentioning
confidence: 99%